Direct-joining of a polylactide acid-hydroxyapatite biocomposite with a titanium alloy - Renan Adauto; Gean Henrique Marcatto de Oliveira; Mário Augusto Morozo; Márcio Antônio Fiori; Leonardo Bresciani Canto (Polímeros)
Abstract A promising yet underexplored alternative for biomedical applications involves incorporating polymer, metal, and ceramic materials into hybrid structures. In this study, a biocomposite consisting of polylactic acid (PLA) with 20 wt% of nearly spherical sub-micron hydroxyapatite (HA) particles was successfully synthesized. The HA particles were uniformly dispersed and distributed within the PLA matrix, leading to a biocomposite with a well-balanced combination of thermal and mechanical properties. This PLA−HA biocomposite was then directly joined through injection overmolding onto a laser-surface-structured titanium alloy Ti6Al4V substrate. The PLA−HA/Ti6Al4V hybrid joints demonstrated robust mechanical anchorage, achieved through the thorough filling of the polymer biocomposite into the micro-scale structures engineered onto the metal surface. This mechanism ensured good lap-shear strength, making these hybrid joints promising candidates for orthopedic applications.